RESEARCH OF BUCKLING PROPERTY ON CORRUGATED STRUCTURE - KONG Bin; YANG JiaYong; ZHOU Bin; WANG Man; ZHANG Long; WANG Bo (Jixie qiangdu)
In this paper,the buckling property of two kinds of corrugated skin structure was analyzed. The influence of radius,depth and number of reinforce slot on buckling load was studied. The constraint of reinforce slot interspace and machinability was also take into consideration. The research shows that the buckling load increases as the depth of reinforce increases. There is a critical line of reinforce slot radius,when being at left side of the line,the buckling load increase as the radius increases,and vice versa. There is a critical surface of reinforce slots number,when under the surface,the buckling load increases as the reinforce slots number increase.